John Denver's Take me home, country roads - Canyon, Christopher; Denver, John. (Nevada City, Calif. : Dawn Publications, 2005)
A picture book adaptation of John Denver's song Take me home, country roads, which celebrates the experience of arriving home to the countryside of West Virginia.
No accompanying cd at Owen County Public Library.
Otterbein PL copy In Memory of Monte Holder
13 21 25 36
Keywords: Children's songs -- Texts; Home -- Songs and music; Country life -- West Virginia -- Songs and music; West Virginia -- Songs and music; Songs